Plant growth regulators as a strategy for growth and yield optimization of Indian mustard (Brassica juncea L.) under different agri-horticultural systems - Soumya, Prakash Bhoi; Sanjay, Singh Rathore; Kapila, Shekhawat; Puspa, Parameswari; Rahul; Dileep, Meena; Parmeswar, Dayal (Plant Science Today, 2026)
India is the world's largest importer of edible oils, with an annual expenditure of approximately USD 10.5 billion, while ranking fourth in global vegetable oil production. Despite this production status, India remains heavily dependent on imports to meet its edible oil demands. Oilseed production in India is rainfed and has shown stagnation, with cultivation largely undertaken by marginal and smallholder farmers. Agricultural productivity can be enhanced using plant growth regulators (PGRs), which improve physiological responses to environmental stress. The present study investigates the effects of different PGRs-1 % potassium nitrate (KNO3), 200 ppm salicylic acid and 1 % urea on the growth, yield and economic returns of Indian mustard (Brassica juncea L.) under different agri-horticultural systems (AHS). The experiment was conducted at Indian Agricultural Research Institute, New Delhi, in the Rabi season of 2022–2023. It was laid out in a split-plot design with three main-plot treatments (Moringa based AHS, Phalasa based AHS and Karonda based AHS) and four sub-plot treatments (control, 1 % KNO3, 200 ppm salicylic acid and 1 % urea) with 3 replications. Results revealed that 1 % KNO3 significantly improved dry matter accumulation, plant height and numbers of branches, while moringa-based AHS produced the highest yield (18.80 q/ha). Foliar application of 1 % KNO3 resulted in the highest seed yield (18.86 q/ha) and stover yield (58.83 q/ha), outperforming the other treatments. The integration of PGR application with suitable AHS emerged as an effective strategy for enhancing the productivity and resource-use efficiency of Indian mustard, indicating its potential for improving crop yields in India’s oilseed production systems.